Currency movements within and outside a currency union: The case of Germany and the euro area - Nikolaus Bartzsch; Gerhard Rösl; Franz Seitz (Research On Money in the Economy (ROME), 2011)
In this paper, we analyze the volume of euro banknotes issued by Germany within the euro area with several seasonal methods. We draw a distinction between movements within Germany, circulation outside Germany but within the euro area and demand from non-euroarea countries. Our approach suggests that only about 20% of euro notes issued by Germany are used for transactions in Germany. The rest is hoarded (10%), circulates in other euro area countries (25%) or is held outside the euro area (45%).
Keywords: E41; E42; E58; 330; Banknotes; euro; foreign demand; hoarding; transaction balances